2023
DOI: 10.1097/md.0000000000034698
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic risk factors for patients with hepatic sinusoidal obstruction syndrome caused by pyrrolizidine alkaloids

Abstract: Pyrrolizidine alkaloids induced hepatic sinusoidal obstruction syndrome (PA-HSOS) often occurs after consuming herbs or a dietary supplement containing the plant Tu-San-Qi. Limited data exists to identify patients with fatal outcomes for early interventions. We aimed to analyze the predictors for 3-month survival. We retrospectively enrolled PA-HSOS patients in 5 hospitals and extracted data from the onset of PA-HSOS to 36 months. Outcome measurements were 3-month and 36-month survival rates, baseline prognost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…As a result of toxic damage to the hepatic sinusoidal endothelial cells (HSECs), liver enlargement, ascites, and hyperbilirubinaemia occur [84,85]. In the absence of medical treatment, severe consequences of HSOS appear, including fibrosis, cirrhosis, necrosis, and eventually death [86][87][88]. The ingestion of the Gynura japonica (Thunb.)…”
Section: Hepatotoxicitymentioning
confidence: 99%
“…As a result of toxic damage to the hepatic sinusoidal endothelial cells (HSECs), liver enlargement, ascites, and hyperbilirubinaemia occur [84,85]. In the absence of medical treatment, severe consequences of HSOS appear, including fibrosis, cirrhosis, necrosis, and eventually death [86][87][88]. The ingestion of the Gynura japonica (Thunb.)…”
Section: Hepatotoxicitymentioning
confidence: 99%
“…[ 14 ] It has been reported that the mortality rate of adults for PA-induced HSOS ranges from 16% to 40%, with liver failure being the common cause of death. [ 15 ] However, the mortality rate among children remains unknown owing to the limited number of reported cases.…”
Section: Introductionmentioning
confidence: 99%